Readthrough-Promoting Drugs Gentamicin and PTC124 Fail to Rescue Nav1.5 Function of Human-Induced Pluripotent Stem Cell–Derived Cardiomyocytes Carrying Nonsense Mutations in the Sodium Channel Gene SCN5A. (November 2016) - Kosmidis, Georgios; Veerman, Christiaan C.; Casini, Simona; Verkerk, Arie O.; van de Pas, Simone; Bellin, Milena; Wilde, Arthur A.M.; Mummery, Christine L.; Bezzina, Connie R.
Abstract : Background—: Several compounds have been reported to induce translational readthrough of premature stop codons resulting in the production of full-length protein by interfering with ribosomal proofreading. Here we examined the effect of 2 of these compounds, gentamicin and PTC124, in human-induced pluripotent stem cell (hiPSC)–derived cardiomyocytes bearing nonsense mutations in the sodium channel gene SCN5A, which are associated with conduction disease and potential lethal arrhythmias. Methods and Results—: We generated hiPSC from 2 patients carrying the mutations R1638X and W156X. hiPSC-derived cardiomyocytes from both patients recapitulated the expected electrophysiological phenotype, as evidenced by reduced Na + currents and action potential upstroke velocities compared with hiPSC-derived cardiomyocytes from 2 unrelated control individuals. While we were able to confirm the readthrough efficacy of the 2 drugs in Human Embryonic Kidney 293 cells, we did not observe rescue of the electrophysiological phenotype in hiPSC-derived cardiomyocytes from the patients. Conclusions—: We conclude that these drugs are unlikely to present an effective treatment for patients carrying the loss-of-function SCN5A gene mutations examined in this study. Abstract : Supplemental Digital Content is available in the text.